Probiotics Interact With Lipids Metabolism and Affect Gut Health - Wu, Taoying; Wang, Guangqiang; Xiong, Zhiqiang; Xia, Yongjun; Song, Xin; Zhang, Hui; Wu, Yan; Ai, Lianzhong (Frontiers in Nutrition, 2022)
Probiotics have attracted much attention due to their ability to modulate host intestinal microbe, participate in nutrient metabolism or immunomodulatory. Both inflammatory bowel disease (IBD) and bowel cancer are digestive system disease, which have become a global public health problem due to their unclear etiology, difficult to cure, and repeated attacks. Disturbed gut microbiota and abnormal lipid metabolism would increase the risk of intestinal inflammation. However, the link between lipid metabolism, probiotics, and IBD is unclear. In this review, we found that different lipids and their derivatives have different effects on IBD and gut microbes. ω-3 polyunsaturated fatty acids (PUFAs) docosahexaenoic acid, eicosapentaenoic acid and their derivatives resolvin E1, resolvin D can inhibit oxidative stress and reactive oxygen species activate NFκB and MAPk pathway. While ω-6 PUFAs linoleic acid and arachidonic acid can be derived into leukotrienes and prostaglandins, which will aggravate IBD. Cholesterol can be converted into bile acids to promote lipid absorption and affect microbial survival and colonization. At the same time, it is affected by microbial bile salt hydrolase to regulate blood lipids. LDL in blood lipids is easily converted into ox-LDL, thereby promoting inflammation, while HDL has the opposite effect. Probiotics compete with intestinal microorganisms for nutrients or ecological sites and thus affect the structure of intestinal microbiota. Moreover, microbial short-chain fatty acids, bile salt hydrolase, superoxide dismutase, glutathione, etc. can affect lipid metabolism and IBD. In conclusion, probiotics are directly or indirectly involved in lipid metabolism and its impact on IBD, which provides the possibility to explore the role of probiotics in improving gut health.